2021
DOI: 10.2478/prolas-2021-0056
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Cytokine IFNγ, IL-6, and IL-10 Association with Childhood Obesity

Abstract: Childhood obesity carries a high risk of serious life-threatening cardiometabolic diseases in adulthood, which are associated with low-grade inflammation. The aim of the present study was to measure serum cytokine concentrations in obese children recruited during endocrinology consultations and compared to lean control the results. Blood serum concentrations of interferon gamma (IFNγ), IL-1β, Interleukin 6 IL-6, IL-10, and TNF-α were analysed applying Luminex xMap technology with Millipore reagent kits. Statis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
(42 reference statements)
1
1
0
Order By: Relevance
“…25 No significant correlation was observed for IL-10 with the anthropometry in the present work. Similar finding was observed by Kupèa et al 22 Abdelhamid et al 7 stated that low serum level of IL-10 had a significant association with high BMI in diabetic obese children.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…25 No significant correlation was observed for IL-10 with the anthropometry in the present work. Similar finding was observed by Kupèa et al 22 Abdelhamid et al 7 stated that low serum level of IL-10 had a significant association with high BMI in diabetic obese children.…”
supporting
confidence: 86%
“…Lauridsen et al 20 stated that down regulation of mRNA expression of the anti-inflammatory cytokine IL-10 occurred with a gradual increase in BMI. Abnormal low IL-10 concentrations associated with autoimmune and inflammatory disorders were reported by Yao et al 21 Another study by Kupèa et al 22 reported that high level of IL-10 was observed in obese children and adolescents. These discrepancies may be explained as IL-10 may play a dual role in inflammations.…”
mentioning
confidence: 86%